Effect of the Central Radial Groove on the Bearing Pressure Distribution Based on the Artificial Neural Network - sultan, Hussein Sadiq; Khalid, Maher A.; Abdul-Kadhem, Imad (Basrah Journal for Engineering Sciences, 2014)
An experimental study has been implemented to study the effect of the central radial groove on the bearing pressure distribution. This study is based on the artificial neural network in the prediction of the complex and uncertain positions. Both width and depth of the groove have been varied at some magnitudes in order to investigate their effects on the pressure distribution and the stability of the bearing. Also, the effect of the groove parameters on the noise at the bearing situation in the systems have been analyzed and discussed. The results show that the use of neural network in the prediction of some points with range is very powerful in the minimization of the overall cost of groove design.